NURSE ANXIETY: COVID-19 SURVIVORS - Lina Mahayaty; Wijar Prasetyo; Taufan Citra Darmawan (Jurnal Keperawatan Malang, 2021)
Background: Covid deaths-19 continues to increase globally, various attempts have been made by the government to reduce the incidence. Until now the number of deaths is still not diminished. Health workers, especially nurses are at risk of exposure to workers Covid-19. When treating patients with 19 nurses Covid many are experiencing anxiety. Exploring the experiences of nurses who have survived Covid-19 can help reduce nurses 'anxiety during patient care. Therefore, this study aims to explore nurses' anxiety when diagnosed with Covid-19. Purpose: The purpose of this study to gain experience of nurses as survivors Covid-19 Method: This research is a qualitative study with a phenomenological approach. This study involved 6 participants in Surabaya. Result: In this study, three main themes: 1) Fearing death, 2) Worried about the family, 3) Fearing social stigma Conclusion: Nurses as health workers are at risk of being exposed to Covid-19 and experiencing anxiety. There is a need for an increase in the general public's knowledge about Covid-19. A good knowledge will increase public awareness for running the health protocol and no stigmatization of survivors Covid-19, which have an impact on psychological distress. Keyword: Covid-19, Nurse, Anxiety